(E)-N′-(3,4-Dimethoxybenzylidene)-2-(8-quinolyloxy)acetohydrazide–methanol–water (1/1/1) - Zhan-Ling Ma (Acta Crystallographica Section E, 2009)
In the title compound, C20H19N3O4·CH4O·H2O, the Schiff base molecule is almost planar, with a dihedral angle of 1.2 (1)° between the benzene ring and the quinoline ring system. An intramolecular N—H...O hydrogen bond generates an S(6) ring. In the crystal, the methanol and water solvent molecules are linked to the Schiff base molecule via N—H...O, O—H...O, O—H...N and O—H...(O,N) hydrogen bonds.